Informal financial system in sri lanka: special reference to rural areas - Adikari, A.M.P. (University of Jaffna, 2012)
An effective financial system is required to mobilize resource from surplus sector to deficit sector. This service is provided by both formal and informal financial markets in an economy. Informal financial markets provide very important service in meeting financial needs of units who are not deal with the process of formal financial markets. Characteristics of informal financial services in Sri Lanka can be studied under Rural, Urban and Estate sectors. This study examines the informal financial services in Sri Lanka with special reference to rural areas. Primary data and secondary data are used this study. Secondary data are extracted from the documentary sources. Primary data are gathered through questionnaire conducted with a random sample of 100 household drawn from the list of household available with Grama Niladhari. This sample is selected from purposively selected villages namely Deyyanwela, Arama and Aranayake that are located in three different Grama Niladhari divisions of Aranayake Divisional Secretariat area. The data says that Majority of the respondents are engaging in both financial markets, formal as well as informal financial market, while total of 23% respondent engage in informal financial sector. Pawning, trade credit, crop mortgages, single purpose credit services and direct lending are identified as informal credit services in theresearch areas. Direct lending service is the most utilized financial service by the respondents. As evidenced in data, most of the respondents’ reason for preferring informal financial services is closeness and personal relationship. The research reveals that informal financial services are still playing in rural areas though there can be seen strong spread of formal financial services. It is concluded that integrating informal financial market with formal financial market will increase thescope of the financial transactions and create people confidence in the system thereby encouraging those in the informal sector to patronize the formal sector.
Keywords: Crop mortgage; Direct lending; Financial market; Informal financial service; Pawning; Trade credit